Labor Market Issues in the Caribbean : Scope to Mobilize Employment Growth - Kandil, Magda (IMF Working Papers; Working Paper ;, 2014)
The paper examines the determinants of employment growth, drawing on data available across a sample of Caribbean countries. To that end, the paper analyzes estimates of the employment-output elasticity and the response of employment growth to major sources of labor market determinants, in the long and short run. The main determinants of employment include government investment and private sector credit, while the major determinants of external performance are real effective exchange rate, the price of major exporting commodities, the number of tourists, and growth in major trading partners. The paper concludes with a menu of policy recommendations and structural reforms towards sustaining high employment growth and higher living standards in the Caribbean.